“Logística de servicio en la distribución de productos alimenticios de primera necesidad en el cantón Quevedo para la implementación de una Empresa de entregas a domicilio” - Vera Mandich, Klauss Fabrizio (2021)
The present research originates in analyzing the procedures necessary to execute a logistics of food distribution services in the city of Quevedo through route optimizations. The research process involves the resources needed to execute a competitive project in relation to current market offers. Surveys addressed to a certain target population previously established through market studies that allowed to know the needs of the sector and those aspects that merit improvements in the service. The technical and economic analyses required to carry it out form a fundamental part of the process despite the fact that it does not exist within the current market of the place where the investigation was established. Through the technical study, feasible and low-cost solutions were identified, unlike the leading companies in this activity, these solutions include an operational part that involves the use of route optimization schedules that allowed the effectiveness in reducing distances and time. It was necessary to know the financial factors required to implement a company with the characteristics necessary for the proper functioning of the company. The financial analysis identified the values required for decision-making on the implementation of the project by demonstrating an acceptable return on the required resources of the service. Keywords: Route optimization, market research, financial study, home delivery.